CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE ON CHEMICAL INDUSTRY IN INDONESIA - Wildan Dwi Dermawan; Desiana Desiana; Ulfa Luthfia Nanda (FORUM EKONOMI, 2022)
Manufacturing companies in Indonesia are still showing positive performance in several of their sub-sectors, despite being under economic pressure due to the COVID-19 pandemic. One of the sub-sectors that is still showing positive performance is the chemical sub-sector. On the other hand, the processing of Manufacturing Company products causes environmental pollution. Corporate social responsibility is part of a strategic plan that provides support towards sustainable development goals (SDGs) including protecting and protecting the environment. This study aims to analyze the effect of the board of commissioners, gender diversity, profitability, leverage, company age on corporate social responsibility disclosure. The research population is chemical industry sub-sector manufacturing companies listed on the Indonesia Stock Exchange during 2017–2021. Using multiple regression analysis. The results showed that leverage and company age had an effect on corporate social responsibility disclosure, while the board of commissioners, gender diversity, and profitability had no effect on corporate social responsibility disclosure.